Effects of Extrusion on the Available Energy and Nutrient Digestibility of Soybean Meal and Its Application in Weaned Piglets - Ge Zhang; Zhiqiang Sun; Tenghao Wang; Ling Liu; Jinbiao Zhao; Zeyu Zhang (Animals)
Experiments were conducted to investigate the effects of extrusion devices on the available energy and nutrient digestibility of soybean meal (SBM), and further to investigate the impact of different levels of extruded SBM on the growth performance and nutrient digestibility of weaned piglets. In Exp. 1, eighteen crossbreed growing pigs with an initial body weight (BW) of 32.6 ± 2.7 kg were randomly assigned to three treatments, including a corn basal diet, SBM, and extruded SBM diets. In addition, six cannulated pigs (initial BW, 22.3 ± 1.8 kg) were allocated across an 6 × 3 Youden square design. The experimental treatments included a N-free diet and three diets containing 40% of different SBM sources. The results indicated that extrusion reduced the anti-nutritional factors in soybean meal without affecting the digestibility of available energy and nutrients. In Exp. 2, 192 pigs (initial BW, 6.60 ± 0.54 kg) were allocated across four diets supplemented with 0%, 3%, 6%, and 9% extruded SBM. The four treatments were randomized and each comprised six replicate pens containing four boars and four gilts. The results showed that average daily feed intake (ADFI) decreased linearly with the increase in extruded SBM levels from d 0–14 (p < 0.05), and average daily gain (ADG) increased; ATTD was higher in the GE, DM, OM, and CP of piglets in the 9% extruded SBM group (p < 0.05). In conclusion, the extrusion treatment reduced ANFs in SBM, and adding 9% extruded SBM to the diet improved the growth performance of weaned piglets by increasing the digestibility of nutrients.